Clinical and laboratory features distinguishing pandemic H1N1 influenza-related pneumonia from interpandemic community-acquired pneumonia in adults. Issue 3 (20th January 2011) - Bewick, Thomas; Myles, Puja; Greenwood, Sonia; Nguyen-Van-Tam, Jonathan S; Brett, Stephen J; Semple, Malcolm G; Openshaw, Peter J; Bannister, Barbara; Read, Robert C; Taylor, Bruce L; McMenamin, Jim; Enstone, Joanne E; et al.
Abstract : Background: Early identification of patients with H1N1 influenza-related pneumonia is desirable for the early instigation of antiviral agents. A study was undertaken to investigate whether adults admitted to hospital with H1N1 influenza-related pneumonia could be distinguished clinically from patients with non-H1N1 community-acquired pneumonia (CAP). Methods: Between May 2009 and January 2010, clinical and epidemiological data of patients with confirmed H1N1 influenza infection admitted to 75 hospitals in the UK were collected by the Influenza Clinical Information Network (FLU-CIN). Adults with H1N1 influenza-related pneumonia were identified and compared with a prospective study cohort of adults with CAP hospitalised between September 2008 and June 2010, excluding those admitted during the period of the pandemic. Results: Of 1046 adults with confirmed H1N1 influenza infection in the FLU-CIN cohort, 254 (25%) had H1N1 influenza-related pneumonia on admission to hospital. In-hospital mortality of these patients was 11.4% compared with 14.0% in patients with inter-pandemic CAP (n=648). A multivariate logistic regression model was generated by assigning one point for each of five clinical criteria: age ≤65 years, mental orientation, temperature ≥38°C, leucocyte count ≤12×10 9 /l and bilateral radiographic consolidation. A score of 4 or 5 predicted H1N1 influenza-related pneumonia with a positive likelihood ratio of 9.0. A score of 0 or 1 had a positive likelihood ratio of 75.7 for excluding it. Conclusion: There are substantial clinical differences between H1N1 influenza-related pneumonia and inter-pandemic CAP. A model based on five simple clinical criteria enables the early identification of adults admitted with H1N1 influenza-related pneumonia.